Pelatihan Pembuatan Pupuk Bokasi dari Dedaunan Kering Dikelompok Tani Wanita Cerdas Desa Lawelu, Kecamatan. Ulu Moro'o, Kabupaten. Nias Barat - Tuti Ariani Bawamenewi; Fitri Julianti Gea; Richard Alexander Waruwu; Destri Natalis Harefa; Helmin Parida Zebua (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Agriculture is the economic backbone of the people of Lawelu Village, Ulu Moro'o District, West Nias Regency, but dependence on chemical fertilizers is a serious challenge that threatens the sustainability of production. In response to this, training on making bokasi fertilizer based on local dry leaves has been carried out to increase the capacity of members of the "Smart" Women Farmers Group in processing organic waste into environmentally friendly fertilizer. Using a hands-on, hands-on, hands-on participatory approach (learning by doing), the training actively engages participants in all stages of the process, from leaf picking to fermentation. Evaluation of results showed a significant improvement in the knowledge and skills of the participants, as well as the success of fermentation characterized by quality fertilizer characteristics such as fresh aroma, grayish color, and crumb texture. The practice of producing CO₂ gas every week also accelerates the anaerobic fermentation process. This activity not only provides technical benefits, but also strengthens the understanding of the circular economy and the importance of utilizing local materials such as leaves, coconut water, and black soil in building sustainable agriculture. Overall, this training encourages farmers' independence in producing fertilizers and reducing dependence on chemicals, as well as being an inspiring model for organic farming innovations in other villages that have similar potential.